2017
DOI: 10.1038/s41598-017-15897-2
|View full text |Cite
|
Sign up to set email alerts
|

Splenic glucocorticoid resistance following psychosocial stress requires physical injury

Abstract: Mice exposed to chronic subordinate colony housing (CSC) stress show glucocorticoid (GC) resistance of in vitro lipopolysaccharide (LPS)-stimulated splenocytes, increased anxiety and colitis. Similar effects were reported in wounded mice exposed to social disruption (SDR). Here we show that CSC exposure induced GC resistance in isolated and in vitro LPS-stimulated, but not unstimulated, splenocytes, and these effects were absent when CD11b+ splenocytes were depleted. Moreover, re-active coping behaviour during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
53
2
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(72 citation statements)
references
References 44 publications
15
53
2
2
Order By: Relevance
“…In our previous study, we identified bite wounds to be a critical factor in the development of splenomegaly and splenic glucocorticoid (GC) insensitivity, as well as to facilitate spleen cell activation following exposure to the chronic subordinate colony housing (CSC) paradigm 1 . The latter is a pre-clinically validated mouse model for social stress-induced posttraumatic stress disorder (PTSD) [2][3][4] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we identified bite wounds to be a critical factor in the development of splenomegaly and splenic glucocorticoid (GC) insensitivity, as well as to facilitate spleen cell activation following exposure to the chronic subordinate colony housing (CSC) paradigm 1 . The latter is a pre-clinically validated mouse model for social stress-induced posttraumatic stress disorder (PTSD) [2][3][4] .…”
mentioning
confidence: 99%
“…This was indicated by an increase in larger CD11b + cells and a decrease in smaller CD3 + /CD4 + T-and CD19 + B-cells 8 . The dependence of in vitro splenic GC insensitivity on the occurrence of bite wounds was indicated by the inability of in vitro lipopolysaccharide (LPS)-stimulated CD11b + splenocytes, but not splenocytes depleted of CD11b + cells, to respond to the immunosuppressive actions of corticosterone (CORT), the main effector molecule of the hypothalamus-pituitary-adrenal (HPA) axis in rodents 1,2 . Increased spleen cell activation following CSC exposure was indexed by an increased in vitro cell viability of isolated splenocytes from CSC vs. SHC mice, both in the presence and absence of LPS 1 .…”
mentioning
confidence: 99%
“…To minimize risk of wounding, all social defeat sessions were observed continuously, and the animals separated if the social defeat mouse exhibited clear submissive behavior, including submissive posture or freezing. Wounding but not superficial scratches is associated with innate immune response (Foertsch et al, 2017) and through observed defeat sessions no social defeat animals received wounds requiring their exclusion from the experiment. The witness mouse was physically separated from the other mice during the stress protocol by a transparent perforated wall but could observe interactions between its cage mate and the aggressor.…”
Section: Social Defeat/witness Trauma Modelmentioning
confidence: 99%
“…Im Detail zeigten CSC-Mäuse im Vergleich zu Kontrollmäusen in Einzelhaltung (engl. : single-housed controls; SHC) eine Milzzellaktivierung [246,247] und erhöhte zirkulierende pro-und antiinflammatorische Zytokine, einschließlich IL-1β, IL-6, IL-10, Granulozyten-Kolonie-stimulierender Faktor (engl. : granulocyte colony stimulating factor; G-CSF) und MCP-1 [248].…”
Section: Zugrunde Liegende Mechanismenunclassified
“…Wiedererleben der aversiven Details des Traumas [440] Wiederholte soziale Niederlage [2] Vermeidung externer Faktoren die mit dem Trauma in Verbindung stehen [440] Soziale Defizite gegenüber eines unbekannten männlichen Artgenossen (SPAT) [2] Negative Stimmung und Wahrnehmungen [440] Anhaltendes Angstverhalten (EPM, LDB, OF, OA, EPF, SPAT) [2] Übermäßige Unruhe [440] Erhöhte Lokomotion sowie erhöhte Level an Noradrenalin [2] Gastrointestinale Erkrankungen [441] Entwicklung einer spontanen Kolitis; Verschlimmerung einer DSS-induzierten Kolitis [2] Basaler Hypocortizismus [442] Basaler Hypocortizismus [2] Abgeflachter Cortisol-Rhythmus [443] Abgeflachter Corticosteron-Rhythmus [2] Verstärkte Suppression von ACTH durch Dexamethason [444] Verstärkte Suppression von FS-induziertem ACTH durch Dexamethason [2] Verstärkte HPA-Achsen-Antwort gegenüber einem neuen, unbekannten Stressor [106] Verstärkte HPA-Achsen-Antwort während EPF-Exposition [2] Verringerung der prozentualen Treg-Zellen im Plasma [21,445,446] Verringerung der prozentualen Treg-Zellen in peripheren Lymphknoten [2] Komorbidität von Osteoporose und erhöhtes Frakturrisiko [447,448] Beeinträchtigte(r) Knochenmetabolismus [449] und Knochenregeneration [450] Chronische unterschwellige Entzündung [83,95] Systemische Immunaktivierung [242,246,248] Komorbidität von Alkoholmissbrauch und Alkoholabhängigkeit [451,452] Erhöhter Alkoholkonsum [453] Abkürzungen [263,273], um lokale Entzündungspr...…”
Section: Ptbs Cscunclassified